Expresión yzvxz
El profesor se sorprenderá mucho al ver tu solución correcta😉
Solución
Solución detallada
(x∧z)∨(y∧z)=z∧(x∨y)
z∧(x∨y)
Tabla de verdad
+---+---+---+--------+
| x | y | z | result |
+===+===+===+========+
| 0 | 0 | 0 | 0 |
+---+---+---+--------+
| 0 | 0 | 1 | 0 |
+---+---+---+--------+
| 0 | 1 | 0 | 0 |
+---+---+---+--------+
| 0 | 1 | 1 | 1 |
+---+---+---+--------+
| 1 | 0 | 0 | 0 |
+---+---+---+--------+
| 1 | 0 | 1 | 1 |
+---+---+---+--------+
| 1 | 1 | 0 | 0 |
+---+---+---+--------+
| 1 | 1 | 1 | 1 |
+---+---+---+--------+
(x∧z)∨(y∧z)
Ya está reducido a FNC
z∧(x∨y)
(x∧z)∨(y∧z)
z∧(x∨y)